Active Dosimeter‐Based Estimate of Astronaut Acute Radiation Risk for Real‐Time Solar Energetic Particle Events. Issue 9 (9th September 2018) - Mertens, Christopher J.; Slaba, Tony C.; Hu, Shaowen
Abstract: Radiation exposure from solar energetic particle (SEP) events becomes a much greater concern as human exploration extends beyond low Earth orbit and the protective environment of Earth's magnetic field. Free‐space SEP events have an increased impact on mission planning and operations, as countermeasures may be necessary to avoid exceeding astronaut permissible exposure limits. Operational analysis tools are needed to assess acute radiation risk during SEP events in order to determine courses of action during the mission. A methodology has been developed to meet this need, which utilizes onboard vehicle dosimeter measurements to estimate organ dosimetric quantities at astronaut crew locations in real time. The estimated organ doses provide the necessary inputs to acute biological response models that predict radiation‐induced performance decrement and other acute radiation effects. The real‐time SEP organ dose estimation methodology has been combined with an acute biological response model, providing an active dosimeter‐based acute radiation risk model for operational mission planning, and determining radiation exposure mitigation measures for deep‐space exploration missions. This new tool has been developed specifically for National Aeronautics and Space Administration's Orion Multi‐Purpose Crew Vehicle storm shelter environment but could easily be extended to other vehicles. The methodology for estimating SEP organ doses is evaluated and assessed in this paper, and a simulation of the acute radiation responses in the Multi‐Purpose Crew Vehicle storm shelter is shown for the historical October 1989 SEP event. The operational acute radiation risk model will be utilized on National Aeronautics and Space Administration's Exploration Mission 1 and Exploration Mission 2. Key Points: New method was developed to estimate SEP radiation exposure on future exploration missions based on active dosimetry Dosimetry alone is insufficient to characterize SEP radiation risk but must be converted to biological impact The new method is promising; some challenges remain; The approach will be tested on future Orion missions